Capacités vocales des primates non humains, des Homo sapiens et des hominines fossiles : un état de la question - Marion Laporte; Amélie Vialet (Revue de Primatologie)
The articulated language we practice has always fascinated philosophers and scientists, both in terms of the anatomy that makes it possible and the question of its specific nature (i.e., exclusive to our species). This article provides a historical overview of the main studies conducted since antiquity, highlighting paradigm shifts and the evolution of issues. In the 19th century, two proposals would significantly influence research: Paul Broca's identification of the seat of articulated language in the cerebral cortex and Robert Willis's argument about the importance of the length of the vocal tract and its variations in explaining vowel production, paving the way for phonetic studies. A century later, it became possible to visualize them in an acoustic space and Gunnar Fant proposed the source-filter theory for the production of contrasting sounds. In this context, Philip Lieberman demonstrated that the descent of the larynx is a necessary condition for language, explaining why monkeys and Neanderthals lack it. This proposition dominated for half a century, hindering research on the vocal production of non-human primates used as a model to address the capacities of fossil hominins. The recent demonstration of vocal tract dynamics in mammals, including primates, and a shared maximal acoustic space for all now allows us to consider that it is not the size of the pharynx that is crucial but rather the control of speech articulators. This paradigm shift, liberating for studies on non-human primates whose anatomical and physiological peculiarities need better understanding, makes it even more challenging to appreciate the emergence of speech during human evolution based on fossil material, which retains little information about the involved articulators (mainly the mandible, tongue, and lips).